Multiple Solution Results for Perturbed Fractional Differential Equations with Impulses. (12th November 2020) - Li, Peiluan; Xu, Liang; Li, Peiyu; Wang, Hui
Abstract : The multiplicity of classical solutions for impulsive fractional differential equations has been studied by many scholars. Using Morse theory, Brezis and Nirenberg's Linking Theorem, and Clark theorem, we aim to solve this kind of problems. By this way, we obtain the existence of at least three classical solutions and k distinct pairs of classical solutions. Finally, an example is presented to illustrate the feasibility of the main results in this paper.